Representações da Leitura em Manuais Didáticos de Língua Portuguesa - Manuella Felicissimo (2009)
This study is aimed at analyzing the representations of reading based on two Portuguese schoolbooks for what in Brazil is called Ensino Médio Português: Linguagens (2003), by William R. Cereja and Thereza A. C. Magalhães, and Português: de olho no mundo dotrabalho (2005), by Ernani Terra and José de Nicola, both published in a single volume. Resorting to the French theory of discourse analysis and to Greimas semiotics, we intended to investigate reading activities of the books chosen, so as to apprehend intra and interdiscursive mechanisms of meaning constitution. Concerning the first mechanisms, we investigated the modalities, the values, the projections of person and tense, as well as the themes that are linked to the discursive formations. Regarding the interdiscursive mechanisms, we interpreted such aspects in relation to the history (memory) of reading, dealing with the ideological (social) aspect and the function of reading in schools presently.The results of our analysis showed that: a) the reading activities have an imperative character (both in a linguistic and in a pragmatic approach); b) there is a hierarchical or a power relationship between the author of the schoolbook and the student; c) there is a process that regulates the possibilities of meaning construction, which tends to privilege what is known as paraphrastical reading in both schoolbooks. Facing these results, we found out that school reading is, primarily, a useful and functional practice, related to the formation of the reader asa citizen and the preparation for the labor market (for example, through the selection process as the vestibular in Brazil), being mostly based on grammatical tradition. On the other hand, we verified, in reading discourse, a movement that breaks with tradition, especially under therelevant influences (from 1980 on) of some linguistic theories (such as discourse analysis, sociolinguistics and textual linguistics). It was also possible for us to observe that the knowledge that is legitimated by the reading activities examined promotes what is called school linguistic identity. We could also figure out that the whole process is related tosocial needs, that is, to what society considers as essential knowledge in order to allow, somehow, social homogeneity. The underlined values, the selection process of certain texts and also the silenced aspects showed us that school reading and the discourse that is builtabout it belongs, in ideological terms, to the dominant discourse, as we had already predicted.